THE ANALYZIS OF EFFICIENCY AND OPTIMIZATION OF COMBINED DEVICE FOR THERMOUTILYZING BOILER SYSTEM - Stepanova, A. (Energy and Automation, 2016)
Results of the analyzis of efficiency and optimization of combined device for thermoutilyzing boiler system are exposed. It is supposed to be used for heating of water and blast gas. For analysis author has used complex methods, the elements of exegetic approach combining with graph theory, theory of linear systems and methods of multilevel optimization.